The Application of Asset Allocation Strategy Using Panin Mutual Fund Products in 2005-2009 Period of Investment - Suryanto, William (Journal of Business and Management, 2012)
Most investors simply compare their portfolio returns to the market performance, however to compare which one is better investment is by comparing the risk adjusted return of the investments. One of the strategies that should be applied by investors that also calculated for the risk of the investment is an asset allocation strategy. In this research, the author combined the asset allocation strategy with Buy-and-Hold principle and Rebalancing Process as the comparison of risk adjusted return with the investment that in line with IDX performance. The result is the application of asset allocation strategy that combined with Buy-And-Hold and Rebalancing Process will generate better risk adjusted return performance compared to portfolio that invested in line with IDX performance measured with Sharpe, Treynor, and Jensen ratio.The best performance is shown by portfolio that invest with asset allocation strategy that combined with quarter rebalancing process and the worst is shown by portfolio that invested in line with IDX since the portfolio will generate the highest risk and beta portfolio among others. In conclusion, during 2005-2009, asset allocation strategy performs better result compared to IDX performance. Asset allocation strategy that combined with rebalancing process of 3 months period gives the best result of risk adjusted return analysis using Sharpe, Treynor and Jensen measurement. The rebalancing process will reduce the risk during the investment because by applying rebalancing process the investors will be forced to apply Ã¢â‚¬Å“Buy Low, Sell HighÃ¢â‚¬Â principle and do not have to panic or doing the opposite for the principle in uncertain investment world Keywords : asset allocation strategy, product, IDX, panin mutual fund, investment.